Meibomian Gland Carcinoma: A Rare Case Report - Shivyogi R. Kusagur; S. Sanjana (Journal of the Scientific Society)
About 5% of malignant eyelid tumors are meibomian gland carcinoma, an uncommon but potentially lethal tumor. We report the case of a 64-year-old male who presented with complaints of swelling with ulceration over the right upper eyelid for the past 2 years. On examination, a solitary painless oval-shaped tumor with nodular surface was visible at the right upper eyelid margin extending up to palpebral conjunctiva with ulceration over it. We have performed tumor excision. Cutler–Beard procedure was used to fix the defect. Histopathology results confirmed it to be moderately differentiated meibomian gland carcinoma.